2009
DOI: 10.1359/jbmr.090523
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Expenditures Associated With Skeletal Fractures Among Medicare Beneficiaries, 1999–2005

Abstract: Fractures impose substantial burdens, in terms of both costs and health, on individuals and health care systems. This is particularly true for older Americans and the Medicare system. The objective of this study was to estimate the costs of care associated with selected fractures among Medicare beneficiaries. This was a retrospective, person-level, pre/postfracture analysis using administrative data. The study used Medicare claims data from 1999 through 2005 for a 5% sample of Medicare beneficiaries. The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 17 publications
7
56
0
Order By: Relevance
“…In summary, these herbs can promote bone healing, prevent bone loss, relieve pain, reduce inflammation and promote circulation. A previous study analyzing Medicare claims data in the United States found that fractures are associated with substantial increases in health services utilization and costs for the first 6 months after the occurrence of fractures (Kilgore et al, 2009). Another study using the Population Health Research Data Repository for Manitoba, Canada also found that there are large incremental health care costs associated with incident fractures in Canada (Leslie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these herbs can promote bone healing, prevent bone loss, relieve pain, reduce inflammation and promote circulation. A previous study analyzing Medicare claims data in the United States found that fractures are associated with substantial increases in health services utilization and costs for the first 6 months after the occurrence of fractures (Kilgore et al, 2009). Another study using the Population Health Research Data Repository for Manitoba, Canada also found that there are large incremental health care costs associated with incident fractures in Canada (Leslie et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…273 Care of the patient with a distal radius fracture is also costly: A cost of US$7788 (between years 2000 and 2005) has been estimated for a Medicare patient with a distal radius fracture. 274 Despite their frequency, treatment of distal radius fractures in elderly patients is controversial 275 …”
Section: Distal Radius Fractures Simon C Mears Md Phd (Harry Hoyenmentioning
confidence: 99%
“…[1][2][3][4][5] Recent data from a cohort of 208,094 patients from the United States revealed that the radius was the most common long bone to fracture. 6 DRF accounts for one-sixth of all emergency department visits 6,7 and 26%-46% of all skeletal fractures observed in the primary care setting. [8][9][10][11][12][13] Typically, a DRF is characterized by a low-energy fracture occurring approximately 2 cm above the distal articular surface of the radius at the junction where the cortical bone becomes thinner and is reinforced by the trabecular bone network.…”
Section: Introductionmentioning
confidence: 99%